The names of decapod and stomatopod Crustacea from Tahiti, French Polynesia, established by Anthony Curtiss in 1938 and 1944 - Ng, Peter K. L.; Eldredge, Lucius G.; Evenhuis, Neal L. (Zootaxa, 2011)
In two poorly known books published in 1938 and 1944, Anthony Curtiss described 21 species of decapod and stomatopod crustaceans from Tahiti. Of these, 20 are found to be junior synonyms of well-known shallow-water species. One species, however, Cancer raihoae Curtiss, 1938, is a possible senior synonym of Portunus hawaiiensis Stephenson, 1968 (Portunidae).